2009
DOI: 10.1073/pnas.0813156106
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical assessment of evolutionary changes in the lepidosaurian skull

Abstract: The lepidosaurian skull has long been of interest to functional morphologists and evolutionary biologists. Patterns of bone loss and gain, particularly in relation to bars and fenestrae, have led to a variety of hypotheses concerning skull use and kinesis. Of these, one of the most enduring relates to the absence of the lower temporal bar in squamates and the acquisition of streptostyly. We performed a series of computer modeling studies on the skull of Uromastyx hardwickii, an akinetic herbivorous lizard. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 33 publications
8
70
1
Order By: Relevance
“…The lower temporal bar, secondarily acquired in Sphenodon [66], [76]–[80] as well as in the common ancestor of archosaurs like crocodiles [66], [80], [81], is under compressive strain during all bites. This is consistent with previous suggestions that it provides a brace [66], [79], [82] that contributes to skull robusticity, and in large theropods such as Tyrannosaurus rex Osborn, 1905 and Allosaurus fragilis Marsh, 1877 this would be important as they would likely generate extremely large biting forces and experience heavy cranial loading [4], [83]. The corollary is that reptiles that lack a lower bar do not need a brace in this location.…”
Section: Discussionmentioning
confidence: 99%
“…The lower temporal bar, secondarily acquired in Sphenodon [66], [76]–[80] as well as in the common ancestor of archosaurs like crocodiles [66], [80], [81], is under compressive strain during all bites. This is consistent with previous suggestions that it provides a brace [66], [79], [82] that contributes to skull robusticity, and in large theropods such as Tyrannosaurus rex Osborn, 1905 and Allosaurus fragilis Marsh, 1877 this would be important as they would likely generate extremely large biting forces and experience heavy cranial loading [4], [83]. The corollary is that reptiles that lack a lower bar do not need a brace in this location.…”
Section: Discussionmentioning
confidence: 99%
“…Curtis et al, 2010;Koolstra and Tanaka, 2009;Moazen et al, 2009;Rayfield, 2007;Strait et al, 2007). Such computer models are often based on high resolution computed-tomography (CT) scan data and are thus geometrically accurate.…”
Section: Introductionmentioning
confidence: 99%
“…These values have been used in previous studies that involved FEA to assess patterns in nonmammalian tetrapod skull evolution (e.g. Moazen et al, 2008;Moazen et al, 2009). Further, Dumont et al (Dumont et al, 2009) demonstrated that FEA can be a useful tool for comparisons of shapes, even in the absence of knowledge on the exact material attributes in vivo.…”
Section: Processing Of the Hrct Data And Finite Element Modelingmentioning
confidence: 99%